Meneladani peran dan kontribusi Ibnu Thufail dalam peradaban Islam - Hidayah, Fefi Nailil (Maliki Interdisciplinary Journal, 2024)
In the history of Islamic civilization, many figures have played crucial roles in developing thought, knowledge, and culture. Among them is Abu Bakr Muhammad ibn Abd al-Malik ibn Muhammad ibn Muhammad ibn Tufail al-Qaisi, known as Ibn Tufail. He was a prominent philosopher, physician, scientist, and writer from Al-Andalus in the 12th century. Ibn Tufail's presence in the history of Islamic civilization reflects the diversity and intellectual advancement that characterized Al-Andalus during its golden age. His works and legacy not only influenced his own era but also had a significant impact on philosophical and scientific thought in both the Islamic world and Europe. Through a thorough analysis, we will explore how Ibn Tufail's ideas and works influenced the development of knowledge in the Islamic world and Europe. This discussion aims to provide a comprehensive understanding of Ibn Tufail's role in the progress of Islamic civilization and to appreciate his invaluable contributions in shaping thought and knowledge in both the Muslim world and beyond. By understanding Ibn Tufail's intellectual journey and daily life, we can deeply appreciate the cultural and intellectual wealth he left behind and draw inspiration from his spirit in seeking truth and expanding the boundaries of human knowledge.